Energy democracy : advancing equity in clean energy solutions - Fairchild, Denise; Weinrub, Al; Horowitz, Diego Angarita; Baker, Isaac; Benander, Lynn (Island Press, 2017)
A global energy war is underway. It is man versus nature, fossil fuel versus clean energy, the haves versus the have-nots, and, fundamentally, an extractive economy versus a regenerative economy. The near-unanimous consensus among climate scientists is that the massive burning of gas, oil, and coal is having a cataclysmic impact on our atmosphere and climate, and depleting earth's natural resources, including its land, food, fresh water and biodiversity. These climate and environmental impacts are particularly magnified and debilitating for low-income communities and communities of color that live closest to toxic sites, are disproportionately impacted by high incidences of asthma, cancer and rates of morbidity and mortality, and lack the financial resources to build resilience to climate change. Energy democracy tenders a response and joins the environmental and climate movements with broader movements for social and economic change. Energy democracy is a way to frame the international struggle of working people, low income communities, and communities of color to take control of energy resources from the energy establishment and use those resources to empower their communities--literally providing energy, economically, and politically. Energy democracy is more important than ever as climate and social justice advocates confront a shocking political reality in the U.S. This volume brings together racial, cultural, and generational perspectives. This diversity is bound together by a common operating frame: that the global fight to save the planet--to conserve and restore our natural resources to be life-sustaining--must fully engage community residents and must change the larger economy to be sustainable, democratic, and just. The contributors offer their perspectives and approaches to climate and clean energy from rural Mississippi, to the South Bronx, to Californian immigrant and refugee communities, to urban and semi-rural communities in the Northeast. Taken together, the contributions in this book show what an alternative, democratized energy future can look like, and will inspire others to take up the struggle to build the energy democracy movement.